POISONOUS BREATHS AND CONTAMINATED POTIONS - Misbah, Samreen; Hisam, Aliya; Qamar, Khadija (Pakistan Armed Forces Medical Journal, 2022)
Clean air, clear blue sky, chirping sounds of humming birds, return of multi-coloured pheasants, and peaceful calm streets devoid of the traffic hustle and bustle were some hallmarks of the COVID-19 lockdown. This led to specific pertinent questions: Is it possible to create a society where everyone has access to clean air? Where do economies place a premium on health and happiness, where people have control over their health and the health of the Earth, and cities are liveable? Shall we think about our Earth? Should we consider the air we breathe as clean air or the water we drink as clean water? The World Health Organization (WHO) hosted the First World Health Assembly in 1948. Since 1950, the assembly declared 7th April to be World Health Day. World Health Day commemorates the creation of WHO and is used by the organisation to bring global attention to a topic of immense importance to global health each year. This year, on 7th April 2022, the WHO theme was ‘Our Planet, Our Health’.